Responses of winged bean (Psophocarpus Tetragonolobus) to Mycorrhiza Inoculation in pot and field trials - Hashim, Azizah; M., Omar; I. R., Hall (Universiti Putra Malaysia Press, 1996)
Two greenhouse experiments and one field trial were conducted to provide information on the possibility of exploiting the beneficial effects of vesicular-arbuscular mycorrhizal fungi in Malaysian agriculture. In the first study, winged bean (Psophocarpus tetragonolobus) was grown in steam-sterilized Serdang soils and the development of the endophytes evaluated fortnightly. The second experiment was conducted in unsterilized Serdang and Munchong soils respectively with three levels ofP and/or inoculated with Acaulospora laevis, Glomus macrocarpum, Glomus mosseae, a mixture of Glomus species and Scutellospora calospora. All inocula, except for S. calospora, significantly enhanced growth throughout the course of the experiments and increased N, P and K concentrations in the plant tissues. G. mosseae was superior to the rest. In the field trial, Acaulospora laevis, Scutellospora calospora and Glomus mosseae were inoculated into winged bean grown in unsterilized field soil, with or without phosphate fertilizer. Inoculation of winged bean with G. mosseae significantly (P < 0.05) increased inflorescence formation (4.5/plant) , particularly at an intermediate level (60 kg ha-1 ) of P fertilizer.